Exhaled nitric oxide in cystic fibrosis: relationships with airway and lung vascular impairments - Hubert, D; Aubourg, F; Fauroux, B; Trinquart, L; Sermet, I; Lenoir, G; Clément, A; Dinh-Xuan, A T; Louis, B; Mahut, B; Delclaux, C (The European respiratory journal, 2009)
A reduction of exhaled nitric oxide (NO) fraction and endothelial-mediated dysfunction have been reported in cystic fibrosis (CF). The aims of the present study were to search for relationships between flow-independent NO exchange parameters (bronchial NO flux (J'(aw,NO)) and alveolar NO concentration (C(A,NO))) and lung function tests characterising airflow limitation and pulmonary vascular bed (capillary blood volume and physiological dead space/tidal volume (V(D)/V(T)) ratio on exercise). In total, 34 patients (16 children, 18 adults) with CF, without resting pulmonary hypertension, underwent spirometry, exhaled NO measurement (multiple constant flow analytical method), gas transfer assessment (carbon monoxide and NO, allowing the calculation of capillary volume and membrane conductance) and a graded exercise test with oxygen uptake (V'(O(2))), carbon dioxide production (V'(CO(2))) and arterial blood gas evaluations. Both J'(aw,NO) and C(A,NO )correlated positively with airflow limitation. C(A,NO) correlated positively with capillary/alveolar volume. During exercise, criteria of mild pulmonary vascular disease were evidenced in some patients that participated in exercise limitation (negative correlation between physiological V(D)/V(T) and peak V'(O(2))). C(A,NO )at rest correlated positively with these parameters of wasted ventilation during exercise (physiological V(D)/V(T), minute ventilation (V'(E))/V'(CO(2)) at ventilatory threshold and V'(E)/V'(CO(2)) slope). Flow-independent exhaled NO parameters are linked to airway and early vascular diseases in patients with CF.